Effect of Hybrid Layer and Thickness on Stress Distribution of Cervical Wedge-Shaped Restorations - Eliguzeloglu, Evrim; Eraslan, Oguz; Omurlu, Huma; Eskitascıoglu, Gurcan; Belli, Sema (European Journal of Dentistry, 2010)
Objectives: The aim of this finite elemental stress analysis study was to evaluate the effect of a hybrid layer and the hybrid layer thickness on the shear stress distribution in mandibular premolar teeth under occlusal loading.Methods: The mandibular premolar tooth was selected based on the anatomical measurements suggested by Wheeler. The analysis was performed with a computer with the SAP 2000 structural analysis program. Three different mathematical models were evaluated; 1) composite restoration without a hybrid layer 2) composite restoration with a 1.5 μm thick hybrid layer and 3) composite restoration with a 3 μm thick hybrid layer. A total of 200 N of occlusal loading force was simulated from the buccal tubercule and central fossa of the premolar tooth. The findings were drawn by the Saplot program.Results: In model B, the output showed that hybrid layer reduced the shear stress concentration especially on gingival margin of the composite. Similarly shear stress intensity was decreased by a thick hybrid layer in model C, especially on the gingival margin of the composite.Conclusions: The hybrid layer and its thickness plays an important role on stress distribution and intensity in cervical restorations. (Eur J Dent 2010;4:160-165)
Keywords: Finite element analysis; Hybrid layer; Premolar tooth; Non-carious cervical lesion; Composite restoration